Post-financial Crisis 1997/1998: Disclosure of Corporate Governance among Banks in Malaysia - Omar, Siti Aisyah (2008)
This research investigates the comprehensiveness of corporate governance disclosure in the annual reports among banks in Malaysia so as to identify the improvements on corporate governance disclosure after the financial crisis 1997/1998. A sample consisting of 17 foreign and domestic commercial banks operated in Malaysia has been selected based on the list obtained from Bank Negara Malaysia for the purpose of conducting this research. From the analysis of the annual reports, a finding shows that most of the banks have disclosed the corporate governance matters in detail according to the Malaysian Code of Corporate Governance and the Guidelines on Corporate Governance for Licensed Institutions issued by Bank Negara Malaysia (BNM) and the behaviour signals significant improvement in the corporate governance disclosure in the aftermath of the crisis.